The long-run relationship between the stock market and main macroeconomic variables in Poland - Czapkiewicz, Anna; Stachowicz, Marta (Managerial Economics, 2016)
The investigation concerns the problem of whether some macroeconomic variables and the EUR/PLN exchange rate might affect the performance of the Warsaw Stock Exchange. The answer to this question can be obtained from a cointegration analysis. The advantage of testing for cointegration is the identification of a stable long-run relationship between the stock price index, some macroeconomic variables, and the EUR/PLN exchange rate, which can be implemented using various cointegration methodologies. Analysis of the response of one variable to an impulse of another variable is also performed to show the importance of a given variable in a system.